Perancangan Smart Cat Feeder Untuk Pakan Kucing Berbasis Node MCU Menggunakan Aplikasi Blynk - Shandi Noris; Wulan Putri (CV. Multi Kreasi Media, 2026)
The feeding process for pets is generally performed manually. However, not all pet owners have sufficient time to feed their pets due to their busy daily activities. This study discusses the implementation of the Internet of Things (IoT) in the development of an automatic pet feeding system, specifically designed for cats. The proposed system utilizes a microcontroller integrated with several components, including sensors, a servo motor, and an ESP8266 Wi-Fi module for internet connectivity. The collected data are transmitted to a server via the ESP8266 module and displayed through the Blynk application as part of the monitoring system. By using the Blynk platform on a mobile device, users can remotely monitor the food stock and control the feeding process. Furthermore, the system enables feeding schedules to be managed in real time according to the pet’s specific needs.